2003
DOI: 10.1023/a:1023671206976
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(20 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Many studies have shown that oxidation rates in humid environment are relatively higher than in dry environment. [2][3][4][5][6] A possible mechanism is that water vapor retards the formation of protective scale. Extensive works have been done to understand the role of water vapor in impeding the formation of protective Cr 2 O 3 scale, but the explanations remain in qualitative manner.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that oxidation rates in humid environment are relatively higher than in dry environment. [2][3][4][5][6] A possible mechanism is that water vapor retards the formation of protective scale. Extensive works have been done to understand the role of water vapor in impeding the formation of protective Cr 2 O 3 scale, but the explanations remain in qualitative manner.…”
Section: Introductionmentioning
confidence: 99%
“…However, Cr 2 O 3 might be unstable above 1050°C due to its conversion to chromium carbides 1,2 or volatile CrO 3 . 7,8 Another disadvantage is that protective Cr 2 O 3 cannot be formed in highly-reducing, carburizing atmospheres, such as CH 4 -H 2 . Novel Fe-base or Ni-base alloys are often alloyed with Al or Si.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a lot of work [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] has been carried out in an effort to understand the effect of water vapor on the high-temperature oxidation of Cr-containing steels.…”
Section: Introductionmentioning
confidence: 99%